FEATURES OF THE DETERMINATION OF MILITARY CRIMINAL OFFENSES (Bulletin of criminological association of Ukraine, 2023)
The article examines the problems of crime in the military environment, factors that contribute to the emergence of military criminal offenses, issues of prevention and the impact of such offenses on the public and trust in the Armed Forces of Ukraine. Military crimes are the serious threat to security and discipline in the military environment, and undermine confidence in military forces. The study of this topic is aimed at understanding the problem, identifying the features of the military environment that contribute to the emergence of criminal activity, developing effective strategies for crime prevention, and increasing trust in the military. It is argued that the criminality of military personnel should be included in the subject of war criminology research.
Keywords: military criminal offenses; crime; determination; social identity; frontline; criminology of war